From illegal to legal: estimating previous illegal experience among new legal immigrants to the United States - Guillermina Jasso; Douglas S. Massey; Mark Richard Rosenzweig; James P. Smith (Institute for the Study of Labor (IZA), 2008)
This paper develops a framework for estimating previous illegal experience among annual cohorts of new legal immigrants to the United States - using public-use administrative microdata alone, survey data alone, and the two jointly - and provides estimates for the FY 1996 cohort of new immigrants, based on both administrative and survey data. Our procedures enable assessment of type of illegal experience, including entry without inspection, visa overstay, and unauthorized employment. We compare our estimates of previous illegal experience to estimates that would be obtained using administrative data alone; examine the extent of previous illegal experience by country of birth, immigrant class of admission, religion, and geographic residence in the United States; and estimate multivariate models of the probability of having previous illegal experience. To further assess origins and destinations, we carry out two kinds of contrasts, comparing formerly illegal new legal immigrants both to fellow immigrants who do not have previous illegal experience and also to the broader unauthorized population, the latter using estimates developed by DHS (2002), Passel (2002), and Costanzo et al. (2002).
urn:nbn:de:101:1-2008041607
Keywords: F22; 300; Illegal immigration; legal immigration; administrative data; survey data; Migranten; Einwanderung; Illegale Einwanderung; Ethnische Gruppe; USA